Myoepithelioma of the Orbital Apex and Middle Cranial Fossa: Case Report and Review of the Literature. (February 2014) - Hayward, Dustin M.; Yoo, David; Lee, John M.; Wild, Elizabeth; Prabhu, Vikram C.
Abstract Myoepitheliomas are rare tumours that originate from glandular tissues such as the parotid or salivary glands, and less commonly from soft tissues of the head, neck, and other parts of the body. Intraorbital myoepitheliomas generally arise from the lacrimal gland. Intracranial myoepitheliomas are rare. We report a myoepithelioma of the orbital apex that did not originate from the lacrimal gland. It extended to the middle cranial fossa from the orbital apex and involved the dura and adjacent bone. A diagnostic biopsy via a lateral orbitotomy preceded resection. We review the natural course and histopathology of myoepithelial neoplasms, the surgical nuances of approaching an orbital apex tumour with maximal functional preservation, and the optimal management practices of these rare lesions.